Dasar liberalisasi dan hubung kait dinamik antara pasaran saham di negara-negara Asia kian muncul - Sarmidi, Tamat; Baharumshah, Ahmad Zubaidi; Md Nasir, Anuar (Universiti Utara Malaysia, 2002)
This paper analyses the short and long run dynamic interrelationship among four emerging equity markets (Korea, Taiwan, Malaysia and Thailand) and two Asian major equity markets (Japan and Hong Kong). The empirical investigation is conducted in two diferent periods from 1988 to 1991 (preliberalisation) and 1992 to 1997 (post-liberalisation) to investigate the impact of financial reforms and the opening up of the Asian markets. The empirical evidence shows that financial reforms have an impact on the cointegrating relationships between the Asian markets are closely linked with Japan, Hong Kong and among themselves over the post-liberalisation era.